NILAI PERUSAHAAN BESERTA FAKTOR YANG MEMPENGARUHINYA PADA PERUSAHAAN INDUSTRI DASAR DAN KIMIA - Petty Aprilia Sari (KRISNA: Kumpulan Riset Akuntansi, 2023)
The purpose of this study is to analyze the factors that affect firm value using panel data. The value of the company is a very crucial thing in companies that are often associated with stock prices, if the share price is high then the value of the company is also high & the level of acceptance of the owners of the company will be high. Many factors that affect the value of the company, among others, namely Dividend Policy, Debt Policy, Capital Structure, & Liquidity. By using a purposive sampling method of 80 basic & chemical industrial companies for the 2015-2019 period, a sample of 8 companies that meet the criteria, using a total of 40 information observations, were obtained. This study uses panel data regression analysis using the program eviews 9.0. The results of this study show that partially, Debt & Liquidity Policy has a negative effect on Firm Value. Meanwhile, Dividend Policy & Capital Structure has no effect on Firm Value.